1993
DOI: 10.1063/1.354456
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the oxide surface layer on fine iron particles

Abstract: The spin pinning in the oxide surface layer has been observed directly, and it is considered a possible reason why the oxide layer leads to the decrease of the specific saturation magnetization for fine iron particles. The pinning depth has been estimated by means of a Mössbauer effect under an applied field of 6 T in a thermal-cycle process. The Debye temperature of the oxide layer and the temperature dependence of f2/f1 have been obtained, where f1 and f2 are the Mössbauer recoilless fractions for the inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…Furthermore, the area fractions for both samples A and B show no change in the temperature range 5-295 K. This means that the effective Debye-Waller factors, and thereby also the effective Debye temperatures, for the iron core and the iron oxide shell are equal. This is in opposition to the results of some earlier studies [7,8], where it was observed that the iron oxide nanocrystallites had a lower apparent Debye temperature than the α-Fe core, i.e. the iron oxide nanocrystallites were slightly detached from the iron core and could vibrate separately.…”
Section: Stability Of the Oxide Shellcontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the area fractions for both samples A and B show no change in the temperature range 5-295 K. This means that the effective Debye-Waller factors, and thereby also the effective Debye temperatures, for the iron core and the iron oxide shell are equal. This is in opposition to the results of some earlier studies [7,8], where it was observed that the iron oxide nanocrystallites had a lower apparent Debye temperature than the α-Fe core, i.e. the iron oxide nanocrystallites were slightly detached from the iron core and could vibrate separately.…”
Section: Stability Of the Oxide Shellcontrasting
confidence: 99%
“…As a consequence of their technological importance, iron-iron oxide nanoparticles have been investigated for decades. Several types of nanoparticle fabrication and structural and magnetic investigation techniques have been applied, see for instance [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. There seems to be a general agreement that the iron core has the bulk structural and magnetic properties of α-Fe for a wide range of nanoparticle sizes and shapes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…3. Generally, s s decreases with decreasing of particle size of pure iron, due to strong spin pinning induced by surface oxide layers on the fine iron particles [14], while H c increases with decreasing of particle size of pure iron. Since sizes of iron particles increased with loading of Fe, H c did decrease with increasing of iron loading, as shown in Fig.…”
Section: Magnetic Properties Of the Fe/eg Compositesmentioning
confidence: 99%